The high abundances of presolar grains found in the most primitive CM meteorite, Asuka 12169 - Xu, Yuchen; Lin, Yangting; Hao, Jialong; Kimura, Makoto (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites, Thu. 3 Dec. conference object